2013
DOI: 10.1007/s10620-013-2826-3
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Amifostine on High-Dose Methotrexate-Induced Small Intestinal Mucositis in Mice

Abstract: The effect of amifostine plus CF was greater than amifostine or CF alone in preventing high-dose methotrexate-induced intestinal mucositis and improving intestinal recovery in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Kaynar et al demonstrated that oxidant parameters were increased and antioxidant parameters decreased in small intestines of the rats administered MTX, in addition reported marked villus and crypt epithelial damage, mixed inflammatory cell infiltration containing PMNL and eosinophil leukocytes [12]. MTX was reported to cause hyperemia, inflammatory cell infiltration and loss of villus epithelial cells in the small intestines of rats [6]. In another study, MTX has been reported to lead to the cellular loss, severe villus atrophy and PMNL leukocyte infiltration [7].…”
Section: Discussionmentioning
confidence: 99%
“…Kaynar et al demonstrated that oxidant parameters were increased and antioxidant parameters decreased in small intestines of the rats administered MTX, in addition reported marked villus and crypt epithelial damage, mixed inflammatory cell infiltration containing PMNL and eosinophil leukocytes [12]. MTX was reported to cause hyperemia, inflammatory cell infiltration and loss of villus epithelial cells in the small intestines of rats [6]. In another study, MTX has been reported to lead to the cellular loss, severe villus atrophy and PMNL leukocyte infiltration [7].…”
Section: Discussionmentioning
confidence: 99%
“…Animal models, particularly rats, have been used to study toxicities of other therapeutics [24] and diseases, such as nonalcoholic steatohepatitis [25]. Rodent models have been used for pharmacokinetic modeling of methotrexate [26], exploring leucovorin rescue [27], and preclinical studies of investigational interventions to reduce toxicity (including pentoxifylline [28], amifostine [29], melatonin [30], and activators of peroxisome proliferator activator receptor a and g [31]). Critically, the mechanism of MTX crystal formation in the renal tubule was elucidated in monkeys [32], and the concept of enzymatic cleavage of MTX using glucarpidase was first described in a mouse model by Chabner et al in 1972 [33].…”
Section: Other Toxicitiesmentioning
confidence: 99%
“…[ 1 ] Several attempts have been made to ameliorate MTX-induced intestinal damage. [ 4 5 6 7 ] However, the outcomes were not completely satisfactory.…”
Section: Introductionmentioning
confidence: 99%